Humoral immunity in dually vaccinated SARS-CoV-2-naïve individuals and in booster-vaccinated COVID-19-convalescent subjects - Glück, Vivian; Tydykov, Leonid; Mader, Anna-Lena; Warda, Anne-Sophie; Bertok, Manuela; Weidlich, Tanja; Gottwald, Christine; Köstler, Josef; Salzberger, Bernd; Wagner, Ralf; Koller, Michael; Gessner, André; et al. (Infection, 2022)
Background The immune response to COVID-19-vaccination differs between naïve vaccinees and those who were previously infected with SARS-CoV-2. Longitudinal quantitative and qualitative serological differences in these two distinct immunological subgroups in response to vaccination are currently not well studied. Methods We investigate a cohort of SARS-CoV-2-naïve and COVID-19-convalescent individuals immediately after vaccination and 6 months later. We use different enzyme-linked immunosorbent assay (ELISA) variants and a surrogate virus neutralization test (sVNT) to measure IgG serum titers, IgA serum reactivity, IgG serum avidity and neutralization capacity by ACE2 receptor competition. Results Anti-receptor-binding domain (RBD) antibody titers decline over time in dually vaccinated COVID-19 naïves whereas titers in single dose vaccinated COVID-19 convalescents are higher and more durable. Similarly, antibody avidity is considerably higher among boosted COVID-19 convalescent subjects as compared to dually vaccinated COVID-19-naïve subjects. Furthermore, sera from boosted convalescents inhibited the binding of spike-protein to ACE2 more efficiently than sera from dually vaccinated COVID-19-naïve subjects. Conclusions Long-term humoral immunity differs substantially between dually vaccinated SARS-CoV-2-naïve and COVID-19-convalescent individuals. Booster vaccination after COVID-19 induces a more durable humoral immune response in terms of magnitude and quality as compared to two-dose vaccination in a SARS-CoV-2-naïve background.